A mid-Holocene vegetational and anthropogenic record in the Guanabara Bay region, Rio de Janeiro State, SE Brazil, assessed by palynological and charcoal data. Issue 4 (4th July 2017) - Barreto, Cintia F.; Freitas, Alex Da S. De; De Souza, Taísa Camila S.; Vilela, Claudia G.; Barth, Ortrud M.; Baptista Neto, José A.
Abstract: Palynological and charcoal fragment analyses of Guanabara Bay sediments, as well as radiocarbon dating, were carried out on one 220 cm long sedimentary core collected from the northeast sector of the bay, near the São Gonçalo coast. This study aims at recognising and explaining the environmental history of this region during the mid-Holocene, and to identify the anthropogenic influences on it. The palynological data indicate the predominance of ombrophilous forest vegetation in the Guanabara Bay Hydrographic Basin at c . 6500 calendar yearsbp . During this period (pollen zone 1), the concentrations of pollen grains and spores may still have been controlled by the Holocene Maximum Transgressive Event. After a phase of low concentrations of palynomorphs, there was a considerable increase in the accumulation patterns of pollen and spore grains (pollen zone 2). This increase can probably be related to the retreat of the sea level event after the Holocene Maximum Transgressive Event. The 75 cm of the core top (pollen zone 3) provide clear evidence of human influence in the area, which is inferred from the significant reduction in ombrophilous forest pollen grains, the significant increase in herbaceous pollen grains, the presence of exotic pollen types ( Eucalyptus and Pinus ), and high concentration of carbonaceous particles.